E-Assessment Integration in Dance Practice Evaluation : A Case Study in “Merdeka Belajar-Kampus Merdeka” (MBKM) (Lembaga Pengembangan Kinerja Dosen, 2025)
Technological advancement profoundly impacts civilizations, cultures, and educational paradigms, ushering in a new era of innovation and change. As technology becomes deeply ingrained in our daily lives, educational practices must adapt, necessitating creative approaches to learning and assessment for sustainable educational progress. E-assessment emerges as a groundbreaking online-based assessment system poised to tackle the complexities inherent in initiatives like Merdeka Belajar-Kampus Merdeka (MBKM). By embracing e-assessment, educational institutions can customize assessments to suit the unique requirements of MBKM, ensuring seamless integration and alignment with its core objectives. The reliability of e-assessment enables evaluations to occur at any time, from anywhere, by multiple assessors, fostering inclusivity and collaborative learning environments. However, like any innovation, e-assessment presents its own set of challenges. Users must possess adequate digital literacy and access to necessary resources to fully exploit its potential. This collaborative approach not only resonates with the ethos of MBKM but also bolsters its ability to deliver comprehensive and collaborative dance education. In conclusion, the incorporation of e-assessment into dance practice evaluation underscores the transformative potential of technology in education, demonstrating how innovative solutions can enhance educational experiences and empower learners in the digital era.